Information entropy dynamics, self-organization, and cybernetical neuroscience - Fradkov, Alexander (Frontiers in Network Physiology, 2025)
A version of the speed-gradient evolution models for systems obeying the maximum information entropy principle developed by H. Haken in his book of 1988 is proposed in this article. An explicit relation specifying system dynamics for general linear constraints is established. Two versions of the human brain entropy detailed balance-breaking model are proposed. In addition, the contours of a new scientific field called cybernetical neuroscience dedicated to the control of neural systems have been outlined.